Interaction of ketoprofen and frusemide in man. Issue 789 (July 1991) - Wa, T. C.; Lawson, M.; Jackson, S. H.; Hitoglou-Makedou, A.; Turner, P.
Abstract : The effects of ketoprofen on frusemide-induced diuresis, natriuresis and renin release were studied in 12 healthy male volunteers. Each received frusemide 40 mg once daily with either ketoprofen 100 mg twice daily or placebo for two periods of 5 days separated by a treatment-free period according to a randomized, double-blind, cross-over study design. Ketoprofen significantly reduced frusemide-induced diuresis on Day 1 but not on Day 5 of treatment. The natriuresis induced by frusemide on Day 1 or Day 5 of treatment did not differ significantly whether ketoprofen or placebo was administered, although the mean urinary sodium excretion values were consistently lower following ketoprofen. Ketoprofen did not affect the kaliuretic response to frusemide on Day 1 or Day 5 of treatment. The increase in plasma renin activity after frusemide was inhibited by ketoprofen on both Day 1 and Day 5. These results suggest that ketoprofen reduces the diuresis and renin release induced by frusemide, but that the reduction in diuretic response may become less important after their repeated coadministration.